Validation of the importance of neutrophil-to-lymphocyte ratio in non-muscle invasive bladder cancer - Porav-Hodade Daniel; Balan Daniel; Reman Tibor; Balan-Bernstein Noemi; Vida Arpad Oliver; Martha Orsolya (Journal of Men's Health, 2022)
Background and objective: Since the peritumoral inflammatory reaction is of considerable importance in the oncological prognosis of bladder cancer, the neutrophil-to-lymphocyte ratio (NLR) may be a very practical and accessible biomarker in non-muscle invasive bladder tumors. This study aims to analyze parameters of non-muscle invasive bladder tumors and to identify and validate potential tumor markers with a prognostic role in this condition. Material and methods: 463 patients diagnosed with non-muscle invasive urothelial tumors, between January 2016 and June 2020, hospitalized at the Urology Clinic in Târgu Mureș, after transurethral resection of bladder tumor (TURBT) were investigated. Inclusion criteria were: non-muscle invasive tumors (Ta, T1, CIS), neutrophil-to-lymphocyte ratio (NLR) determination 2 weeks prior to TURBT and complete follow-up of patients. NLR cut-off was set at 3. Results: 371 people diagnosed with non-muscle invasive bladder tumors met the inclusion criteria. The mean age of the included patients was 69.96 years (IQR 35–93). 297 (80.05%) were male and 74 (19.95%) were female. 64.95% pTa tumors, 31.26% pT1, 1.07% pTa + CIS, and 2.69% pT1 + CIS, respectively, were identified. Distribution according to Grade: 196 (52.8%) G2, 159 (42.88%) G3 and 16 (4.32%) CIS. 284 (76.5%) patients presented with a single tumor and 87 (23.35%) with multiple tumors; 295 (79.5%) had tumors larger than 3 cm and 76 (20.5%) smaller than 3 cm. 228 (61.4%) presented with recurrence after 3 months after surgery. Overall survival at 5 years was 80.06%. Advanced age at the time of diagnosis correlated with low survival, p = 0.004. The mortality rate was higher among men (20.54%) than among women (17.58%). Statistically, there was a positive relationship between the increased ratio of neutrophils and lymphocytes in people diagnosed with non-muscle invasive bladder cancer and increased mortality rate, p = 0.003. Conclusions: The overall survival of patients with non-muscle invasive bladder cancer was negatively influenced by the advanced age of the patients at the time of diagnosis. Increased preoperative NLR was associated with a higher mortality rate in patients with non-muscle invasive bladder cancers. This assay is an accessible, easy to performand useful biomarker in the prognosis of non-muscle invasive bladder tumors.